DILEMATIKA KEKUASAAN LEMBAGA PERADILAN DAN KEADILAN DALAM FRAME DESENTRALISASI PEMERINTAHAN (SUATU COMMON SENSE) - Subarkah, Ibnu (Jurnal Konstitusi, 2011)
The implementation of the government decentralization makes some implications to the levels of the society, nation, and state life. These implications are caused by the functions of Justice Institution Power, especially the justice institutions at the local/provincial levels, that bear heavy loads. As a result, the interaction between the law and social life plays an important role. The  realization of this role is the extent to which the justice institutions may satisfy various parties, not only the Justice Institution Power which is One Roof System. It is the matter that may be thought together.